V˙O2 linear-onset kinetics spanning steady- and non-steady-state exercise - Robergs, Robert; O’Malley, Bridgette; Dewilde, Anais; D’Auria, Shaun; Krouzecky, Ales (Frontiers in Physiology, 2025)
IntroductionThe traditional method for quantifying the kinetics of the increase in the body’s consumption of oxygen (V˙O2) during exercise transitions to steady state involves application of a mono-exponential function. Anomalies exist to question the validity of this method, as they show the initial (∼1 min) of this V˙O2 response is linear.MethodsFourteen highly endurance trained subjects (12 males, 2 females) completed a ramp incremental cycling protocol, as well as 8 different constant load trials at 43 to 148 % of their critical power (CP).ResultsFor the initial five exercise bouts, the linear fit of the initial segment was significantly more accurate (lower standard error of estimates; SE) compared to the mono-exponential fit (p < 0.001). There were two different systematic profiles of the linear onset (LO) V˙O2 slope from different bouts of increasing exercise intensities; 1) a sustained increase (increased kinetics) (n = 7), and 2) a plateau or decrease (impaired kinetics) (n = 7). Both sub-groups were similar in all measures of cardio-respiratory and muscular endurance.DiscussionThe LO V˙O2 kinetics method is superior to the traditional approach as it was a more valid representation of the initial V˙O2 response, can be applied to both steady and non-steady state exercise intensities, requires less than 2 min of exercise, but across multiple bouts, and identifies more complex physiology than the mono-exponential method. Added research is needed to discern the most valid methods to measure LO V˙O2 kinetics, and to learn more about its physiological determinants compared to the traditional mono-exponential method.